Odpowiedzi

Najlepsza Odpowiedź!
  • Użytkownik Zadane
2009-12-09T19:22:59+01:00
A) 5x+y=7(wyznaczamy x)
5x=7-y
x=(7-y)/5

b)3y-x=3(wyzn. y)
3y=3+x
y=(3+x)/3

3x=y-5(wyzn. x)
x=(y-5)3

d)2y=x+12(wyzn. y)
y=(x+12)/2

e)25x+5y=10(wyzn. x)//5
5x=2-y
x=(2-y)5

f)3x-9y=6(wyzn. y) //3
x-3y=2
-3y=2-x
y=(2-x)/-3

g)4x+2y=8(wyzn. x)//2
2x+y=4
2x=4-y
x=(4-y)/2

h)2(x+y)=6(wyzn. y)//2
x+y=3
y=3-x

i)3(x+1)=2(4-y)(wyzn. x)
3x+3=8-2y
3x=5-2y
x=(5-2y)3
2009-12-09T19:27:38+01:00
A) 5x+y=7(wyznaczamy x)
5x= 7- y
x= 7/5 - 1/5y

b)3y-x=3(wyzn. y)
3y= 3+x
y= 1 + 1/3x

3x=y-5(wyzn. x)
x= 1/3y - 5/3

d)2y=x+12(wyzn. y)
y= 0.5x + 6

e)25x+5y=10(wyzn. x)
25x= 10 - 5y
x= 0.4 - 0.2y

f)3x-9y=6(wyzn. y)
-9y= 6-3x
y= -6/9 + 1/3x

g)4x+2y=8(wyzn. x)
4x= 8 - 2y
x= 2 - 0.5y

h)2(x+y)=6(wyzn. y)
2x + 2y= 6
2y= 6 - 2x
y= 3 - x

i)3(x+1)=2(4-y)(wyzn. x)
3x+3=8-2y
3x=5-2y
x=(5-2y)3